Association of anosmia and neutralizing antibody production in adolescents with SARS-CoV-2. (January 2023) - Gitman, Lyuba; Newman, Daniel; Burak, Bahar; Reilly, Brian K.; Mudd, Pamela
Abstract: Background: To monitor olfactory/gustatory dysfunction and its relationship to SARS-CoV-2 IgG antibody responses in an adolescent population. Methods: Adolescents with changes in olfactory/gustatory functions were enrolled in a 15-month study. The patients were evaluated with 1) SNOT-22, 2) pediatric smell wheel, and 3) SARS-CoV-2 antibody testing. The relationship between these scores and length of anosmia, and the amount of SARS-CoV-2 IgG antibodies were assessed. A brain MRI was performed in cases of persistent special sensory symptoms. Results: Eighteen patients were identified with smell and/or taste complaints. Most of the patients were female (67%) and median age was 15 years (range 11–17). Twelve patients had prior SARS-CoV-2 PCR testing, with only five patients with a positive result. The median SNOT-22 score was 16 (range 0–52) and the median smell wheel score was 6.5 (range 1–11). Patients with taste difficulty were more likely to have a score less than eight. 78% of the patients tested positive for antibodies and there was a strong negative correlation between smell wheel score and antibody level (Spearman, ρ  = −0.798, p  = 0.002). Five patients underwent MRI scan, and all resulted as normal olfactory bulb structures. 66% received nasal corticosteroids. 11 patients presented in follow up. Conclusions: Adolescents presenting to a pediatric ENT clinic during the SARS-CoV-2 pandemic were likely to have prolonged (>6 weeks) symptoms of SARS-CoV-2. The majority do not report positive PCR testing result but do report systemic symptoms including anosmia. This suggests that anosmia may be both a late and prolonged symptom of SARS-CoV-2.